INVESTMENT ANALYSIS OF ADDITIONAL WAREHOUSE AT CEMENT DISTRIBUTE WITH A METHOD OF ANALYTIC HIERARCHY PROCESS - Mawarda, Fidyah; Yuniarti, Rahmi; Azlia, Wifqi (JEMIS (Journal of Engineering & Management in Industrial System), 2016)
Cement Industry for distribute product to consumer has many distributors for each district. One of them an Pasuruan. Pasuruan Distributor has problem that cement’s demands are increasing significantly but  sales are decreasing. This phenomenon happened because of the limited capacity of warehouse about 352 m2. Therefore, they planning to additional warehouse capacity with three options (1) Build new warehouse, or renting warehouse from location (2) A or location (3) B. Distributor should conduct a feasibiility study in order to determine the best option. In this research, Analytic Hierarchy Proces) is used to know the interest rate of each criteria. The criteria are location, wide of location and cost. The results shows that AHP value for building warehouse is 0,327. In the other hand, AHP Value for renting warehouse A and B are  0,448 and 0,225. Based on this comparison, rent A will be the best option as it has the highest AHP.